Pengaruh Kepemimpinan Transformasional dalam Meningkatkan Kinerja Organisasi Pendidikan - Ahmad Muktamar; Faisal; Joaquim Pinto; Hartini (Journal of International Multidisciplinary Research, 2023)
This in-depth research on "The Influence of Transformational Leadership in Improving the Performance of Educational Organizations" uses a qualitative library research method. The main focus of this research is to understand how transformational leadership affects organizational culture, employee motivation, and academic performance in educational settings. The results showed that transformational leadership plays a central role in shaping a positive and inclusive organizational culture, focusing on empowerment, shared vision, and open communication. The dimension of individual empowerment through responsibility and autonomy creates a work climate that supports creativity and growth. A shared vision clearly articulated by the transformational leader provides strong direction for team members, creates meaning in every action, and increases employee engagement. Open communication maintained by transformational leaders provides space for ideas and opinions to flourish, creating a collaborative work environment. The importance of applying transformational leadership in the context of educational organizations is also recognized in the implications of this research. Contributions to the understanding of transformational leadership can help educational leaders develop more contextualized and relevant leadership strategies. The practical implications of this research include the development of leadership training and development programs as well as the formulation of educational policies that support organizational growth and educational quality improvement. Although this study provides a deeper understanding, recognition of the critiques and limitations of previous studies provides a foothold for further research in exploring the complexities of transformational leadership in educational organizations.